A Strategy for Solving the Non Symmetries Arising in Nonlinear Consolidation of Partially Saturated Soils - Di Rado, Hector Ariel (2015)
The main scope of this paper is to present an alternative to tackle the problem of the non symmetries arising in the solution of the nonlinear couple consolidation problem based on a combination of different stress states. Being originally a non symmetric problem, it may be straightforward reduced to a symmetric one, and the conditions in which this reduction may be carried out, are addressed. Non linear saturation-suction and permeability-suction functions were regarded. The geometric model was developed considering an updated lagrangian description with a co-rotated Kirchhoff stress tensor. This description leads to a non-symmetric stiffness matrix and a simple alternative, using a symmetric constitutive matrix, is addressed to overcome this situation. The whole equation system was solved using an open finite element code FECCUND, developed by the authors. In order to validate the model, various examples, for which previous solutions are known, were solved. The use of either a strongly non linear and no symmetric formulation or a simple symmetric formulation with accurate prediction in deformation and pore-pressures is extremely dependent on the soil characteristic curves and on the shear efforts level, as well. A numerical example show the predictive capability of this geometrically non linear fully coupled model for attaining the proposed goal.